Using short-message-service notification as a method to improve acute flaccid paralysis surveillance in Papua New Guinea - Siddhartha Sankar Datta; Berry Ropa; Gerard Pai Sui; Ramzi Khattar; Ravi Shankar Santhana Gopala Krishnan; Hiromasa Okayasu (BMC, 2016)
Abstract Background High quality acute flaccid paralysis (AFP) surveillance is required to maintain polio-free status of a country. Papua New Guinea (PNG) is considered as one of the highest risk countries for polio re-importation and circulation in the Western Pacific Region (WPRO) of the World Health Organization due to poor healthcare infrastructure and inadequate performance in AFP surveillance. The Government of PNG, in collaboration with WHO, piloted the introduction of short-message-service (SMS) to sensitize pediatricians and provincial disease control officers on AFP and to receive notification of possible AFP cases to improve surveillance quality in PNG. Methods Ninety six health care professionals were registered to receive SMS reminders to report any case of acute flaccid paralysis. Fourteen SMS messages were sent to each participant from September 2012 to November 2013. The number of reported AFP cases were compared before and after the introduction of SMS. Results Two hundred fifty three unique responses were received with an overall response rate of 21 %. More than 80 % of responses were reported within 3 days of sending the SMS. The number of reported AFP cases increased from 10 cases per year in 2009-2012 to 25 cases per year during the study period and correlated with provincial participation of the health care professionals. Conclusions Combined with improved sensitization of health care professionals on AFP reporting criteria and sample collection, SMS messaging provides an effective means to increase timely reporting and improve the availability of epidemiologic information on polio surveillance in PNG.